Formation of second-generation stars in globular clusters. Issue 3 (30th July 2019) - Calura, F; D'Ercole, A; Vesperini, E; Vanzella, E; Sollima, A
Abstract: By means of grid-based, 3D hydrodynamical simulations we study the formation of second-generation (SG) stars in a young globular cluster (GC) of mass 10 7 M⊙, the possible progenitor of an old GC with present mass ∼(1–5) × 10 6 M⊙ . The cluster accretes external gas as its first generation (FG) asymptotic giant branch (AGB) stars release their ejecta and SG stars form. We consider two models characterized by different densities of the external gas. In both cases, we find that a very compact SG subsystem with central density $\gt 10^5~M_{\odot }\, pc^{-3}$ forms in the innermost regions of the cluster. The low-density model forms a population of extreme SG stars with high helium enhancement, followed by the formation of another SG group out of a mix of pristine gas and AGB ejecta and characterized by a modest helium enhancement. On the other hand, the high-density model forms in prevalence SG stars with modest helium enhancement. Our simulations illustrate the dynamical processes governing the formation of SG populations in GCs and shed light on the structural properties emerging at the end of this phase. The newly born SG groups have different concentrations, with more extreme SG stars more centrally concentrated than those with less extreme chemical abundances. The very high density of the SG subsystems implies that SG massive stars, if formed, might suffer frequent close encounters, collisions, and gas stripping, thus possibly contributing further gas to the SG formation.